Effect of Benzyltrimethylammonium Ion as a Co-directing Agent on Phase Transitions in a Nanostructure Silica/Surfactant Composite - Alireza Badiei; Hassan Goldooz; Ghodsi Mohammadi Ziarani (E-Journal of Chemistry)
Effect of benzyltrimethylammonium ion as a co directing agent in phase transition from hexagonal to cubic and lamellar mesophases was studied in the constant pH at 130 °C. This phase transformation was carried out in constant surface charge and pore size distribution (2 nm). Influence of BTMA+ ions between head and tail of surfactant and phase transformation were observed by using the XRD and elemental analysis.